Income Distribution, Welfare, and the Patterns of Trade - Reto Foellmi; Björn Hartmann; Josef Zweimüller (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We develop a two-country model of international trade featuring non-homothetic preferences and income inequality, generating a price schedule where cheap necessities coexist with expensive luxury goods. A central mechanism driving price differences is firm's ability to shift fixed costs between countries, shaping trade patterns and welfare. In a North-South setting, poor consumers in the rich country are most negatively affected by this fixed cost shifting, leading to a Manhattan effect. Following mean-preserving redistribution, import volumes rise in the unequal country, and fall in the more equal one.
Keywords: L11; F12; F60; 330; trade; income inequality; nonhomothetic preferences; pricing-to-market